Effect Of Loaded Alkali Metals On The Structural, Basicity And Catalytic Activity Of Zeolite Beta - Wong, Kah Man; Ramli, Zainab; Nur, Hadi (Penerbit UTM Press, 2005)
Zeolite Beta Was Modified By Incorporation Of An Alkali Metal (Na, K, Cs) Through Wet Impregnation Method. The Incorporation Of The Base Guests Has Reduced The Crystallinity And BET Surface Area Of Zeolite Beta, As Evidence By XRD, IR And Nitrogen Adsorption Characterizations. The Framework Structure Was Totally Collapsed At > 8%W/W Loading Of Na And K. Nevertheless, The Concentration Of Base Sites (Basicity) Was Enhanced As Evidence By The Increase In The Amount Of Desorbed CO2 In TPD-CO2 As The Amount Of Metal Loading Increases. The Catalytic Activity Of The Modified Samples Was Tested In Dehydration-Dehydrogenation Of Cyclohexanol. Selectivity Of Cyclohexanone That Is Produced On Base Sites Of Zeolite Beta Increased With The Increase In The Basicity, Consequently Suppressed The Selectivity Of Cyclohexene Produced At Acidic Sites. Cyclohexene Was Obtained As The Dominant Product Due To The Dominant Acidic Properties Of Zeolite Beta. The Ratio Of Cyclohexene To Cyclohexanone Varies With The Increase In The Metal Loading.